2013
DOI: 10.1128/jcm.03368-12
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Biofire FilmArray RP, Genmark eSensor RVP, Luminex xTAG RVPv1, and Luminex xTAG RVP Fast Multiplex Assays for Detection of Respiratory Viruses

Abstract: There are several U.S. FDA-cleared molecular respiratory virus panels available today, each with advantages and disadvantages. This study compares four multiplex panels, the BioFire Diagnostics FilmArray RP (respiratory panel), the GenMark Dx eSensor RVP (respiratory viral panel), the Luminex xTAG RVPv1, and the Luminex xTAG RVP fast. Three hundred specimens (200 retrospective and 100 consecutive) were tested using all four platforms to determine performance characteristics. The overall sensitivity and specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
185
3
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(198 citation statements)
references
References 23 publications
6
185
3
4
Order By: Relevance
“…These findings suggest that the discordant results were frequently reported in samples containing low viral copy. Other studies also indicated that discrepant results between RV assay was quite associated with sample's viral load 7, 8, 19, 20, 21. One samples by AP and three samples by AD identified as INF A positive by additional testing.…”
Section: Discussionmentioning
confidence: 97%
“…These findings suggest that the discordant results were frequently reported in samples containing low viral copy. Other studies also indicated that discrepant results between RV assay was quite associated with sample's viral load 7, 8, 19, 20, 21. One samples by AP and three samples by AD identified as INF A positive by additional testing.…”
Section: Discussionmentioning
confidence: 97%
“…Most of the indicated kits cover multiple viruses and are only approved for qualitative analysis of respiratory specimens. Studies comparing the performances of such kits indicated a particularly high variability for HAdV detection, with inadequate identification of certain HAdV types by some of the tests (196)(197)(198). The monitoring of patients in the immunocompromised setting requires tests permitting reliable detection of all potentially relevant HAdV types in different clinical specimens, as well as accurate quantitative assessment of viral loads.…”
Section: Diagnostic Screeningmentioning
confidence: 99%
“…Although sensitivity and specificities vary between different RVPs such as the BioFire Film Array, GenMark eSensor, Luminex xTAG, and the new NxTAG, a significant advantage is the detection of multiple respiratory pathogens (Table 1). 14 …”
Section: Discussionmentioning
confidence: 99%